Relationship among positive self-esteem, physical literacy, and physical activity in college students: a study of a mediation model - She, Xi; Gao, Tian-Yu; Ma, Rui-Si; Tang, Di; Zhong, Hua; Dong, He-Ling (Frontiers in Psychology, 2023)
Abstract Background In light of the substantial decline in physical activity during college years, this study aims to examine the relationship between positive self-esteem, physical literacy, and physical activity in order to investigate the mechanisms for improving physical activity in college students and to provide a foundation for future interventions. Methods A cross-sectional study design was employed in this study. A total of 5184 Participants, aged between 17 and 21 years (M = 18.97, SD = 1.10), completed the Positive Version of Rosenberg Self-esteem Scales, Perceived Physical Literacy Instruments, and the International Physical Activity Questionnaires. A mediation model was utilized to explore the associations among the three concepts. Results The three regression models were as follows: Physical literacy = 18.03 + 0.98 * Self-esteem, Physical activity = 43.23 + 0.16 * Self-esteem, and Physical activity = 28.18 + 0.11 * Physical literacy. Positive self-esteem, physical literacy, and physical activity were significantly linked with each other. physical literacy mediated 26.93% of the effect, indicating a partial mediator in the relationship between positive self-esteem and physical activity. Conclusions The mediating effect of physical literacy on the relationship between positive self-esteem and physical activity was identified. Our findings support the development of positive self-esteem and physical literacy in college physical education curricula as part of an overall program to address students' physical inactivity at school and in the future. This study provides a new intervention perspective for improving physical inactivity in college students.